(untitled) (PÓS: Journal of the Arts Postgraduation Program at EBA/UFMG, 2025)
This article aims to bring different corporalities and their experiences in contemporary religious practices, specifically in terreiro religions, to the center of the debate. Dissenting bodies, here taken to look at the pombagiras, help us debate real or fantasy notions of monstrosities and normalities, of female performances and what is vetoed and encouraged in these. By choosing to analyze the dissidences of performances and corporeality through elements considered transgressive, we seek to expose the contradictions, complexities and ambivalences of what and how these marginal entities of no less marginalizable beliefs present themselves and, thus, navigating through known colonial ecologies, propose visions more based on decoloniality.